Coulmannia rossensis sp. n. (Isopoda, Asellota, Paramunnidae) from the Ross Sea, Southern Ocean - Choudhury, M. (2011)
A new species of Coulmannia, C. rossensis, is described from the Ross Sea, Antarctica. It is most similar to C. ramosae Castelló, 2004, but can easily be distinguished from this species by the males yielding a pair of granulate humps on the dorsum of the pereonites 1-6 and a single granulate hump on the pereonite 7 and the free pleonite. Coulmannia rossensis sp. n. is sexually dimorphic. Th e dorsal sculpture of the female bodies yield a single granulate hump on all the pereonites and free pleonite. Th e species of the genus Coulmannia are restricted to the Southern Ocean, and C. rossensis sp. n. is the fourth species included in it. © M. Choudhury et al.